1995
DOI: 10.1093/oxfordjournals.humrep.a135773
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric outcome of 424 pregnancies after intracytoplasmic sperm injection

Abstract: An evaluation of the outcome of pregnancies resulting from intracytoplasmic sperm injection for severe male factor infertility was conducted by analysing the data obtained from the patients and/or their obstetrician/gynaecologist on standardized questionnaires. The data from 424 pregnancies between April 1991 and September 1994 were analysed. Early pregnancy loss before 16 weeks occurred in 99 cases (23.3%), including 48 clinical abortions (11.3%), 47 subclinical pregnancies (11.1%) and four ectopic pregnancie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
1
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(22 citation statements)
references
References 0 publications
4
16
1
1
Order By: Relevance
“…Similar results were also recorded in children born with frozen/thawed ICSI embryos, but the numbers for epididymal and testicular spermatozoa were too small. This incidence of major and minor congenital malformations using sperm of all categories is consistent with the ones reported previously for ICSI 11,15,16 and IVF, 15,16 but it is also within the range observed in the general population. 17,18 However, the definition of major and minor malformations is of critical importance.…”
Section: Genetic and Malformation Riskssupporting
confidence: 92%
See 1 more Smart Citation
“…Similar results were also recorded in children born with frozen/thawed ICSI embryos, but the numbers for epididymal and testicular spermatozoa were too small. This incidence of major and minor congenital malformations using sperm of all categories is consistent with the ones reported previously for ICSI 11,15,16 and IVF, 15,16 but it is also within the range observed in the general population. 17,18 However, the definition of major and minor malformations is of critical importance.…”
Section: Genetic and Malformation Riskssupporting
confidence: 92%
“…10 The perinatal outcome of children born after ICSI was not compromised, because the mean gestational age and mean birth weight for single pregnancies were similar to those observed in the general population, whereas they were significantly lower in high order multiple pregnancies. 4 These findings for ICSI babies agree with those observed by Wisanto et al 11,12 but also with those reported for IVF babies from cer- tain registries. 13 It is noteworthy that no significant differences in perinatal outcome were observed between children born after ICSI using ejaculated, epididymal, or testicular sperm and those born using frozen/thawed embryos.…”
Section: Perinatal Outcome and Icsi Pregnancysupporting
confidence: 87%
“…To answer this question, we selected several individual mouse spermatozoa with severe head abnormalities, injected each one into the cytoplasm of a mature oocyte, and followed the products through to maturity. The procedure of direct intracytoplasmic sperm injection (ICSI) is not itself teratogenic in either humans [13,14] or mice [15,16]. For the present study, we used the BALB/c mouse, in which 60-80% of mature spermatozoa have deformed heads (nuclei) [5,17], as a model.…”
Section: Introductionmentioning
confidence: 99%
“…The major concerns with the IVF procedure are the risk of multiple births, preterm deliveries and the delivery of children small for gestational age 1, 2. The same increased risks exist when intracytoplasmatic sperm injection (ICSI) is used 3. However, the risk of developing serious malformations after the IVF procedure seems to be small.…”
mentioning
confidence: 99%